POTENSI BEBAN PENCEMAR (PBP) AIR ASAL LIMBAH PETERNAKAN DI KOTA BANJARMASIN - Danang Biyatmoko (Universitas Lambung Mangkurat, 2012)
The research aims to identify and inventory the potential pollutant sources and calculate the pollutant load from livestock waste water in the river that passes through the city of Banjarmasin. The study was conducted based on a survey sampling and determination of the observation point in the five districts in the city of Banjarmasin. Determination of pollutant sources is observed Coli total, N total, P total and BOD. The results showed that lead to type activity peternakann Barito waste in the watershed and includes Martapura and slaughtering of livestock farming in both the RPH, RPU, and other cattle abattoir. Estimates of potential pollutant load (PBP) from livestock waste in the city of Banjarmasin include pollutant source in the form of Colli total reached 20.07 x 109/day, N Total 2.62 kg day, P Total 1.26 kg/day and BOD reaching 1018.93 kg/day. Key words: potential pollutant loads, livestock waste, river, Banjarmasin